The 2014 hypertension guidelines: implications for patients and practitioners in Asia. Issue 2 (26th November 2015) - Angeli, Fabio; Reboldi, Gianpaolo; Verdecchia, Paolo
Abstract : Hypertension is a global public health issue and a major cause of morbidity and mortality. Because of population growth and ageing, the number of people with uncontrolled hypertension rose from 600 million in 1980 to nearly 1 billion in 2008. Furthermore, the number of adults with hypertension in 2025 has also been predicted to increase by about 60% to a total of 1.56 billion. The prevalence of hypertension in most Asian countries has increased over the last 30 years and more dramatically in the last 10 years. Several factors contributed to such changes in Asia, but acculturation to Western lifestyle, modernisation and urbanisation are considered key contributing factors. There are some unique features in regards to cardiovascular risk in Asia. Specifically, Asian regions have disproportionately higher mortality and morbidity from stroke compared with Western countries. Furthermore, the relationship between blood pressure level and risk of stroke is stronger in Asia than in Western regions. Although evidence-based and qualified guidelines for hypertension diagnosis and management have been released recently from Europe and North America, the unique features of Asian patients with hypertension raise concerns in regards to the real clinical applicability of Western guidelines in Asian populations. Specifically, it is not yet clear to what extent the new blood pressure target proposed by Western guidelines for high risk and elderly hypertensive individuals apply to Asian populations.